Análisis De La Percepción Ciudadana Sobre La Atención Realizada Por La Superintendencia De Transporte A Través Del Chat Virtual De La Organización (2024)
This thesis project analyzes citizen perception regarding the service provided by the Superintendence of Transportation through its virtual chat, using data generated by the Tawk.to tool from each interaction between customer service agents and users. For the analysis, the chat history corresponding to the months from January to October of 2024 was uploaded to an Azure Data Lake (a cloud storage service provided by Microsoft Azure) to be accessed through a Python notebook.